VAS starptautiskās lidostas "Rīga" mārketinga komunikācijas analīze 2022. gadā - Jermolajeva, Kristīne (Latvijas Universitāte, 2023)
Bakalaura darba “VAS starptautiskās lidostas “Rīga”mārketinga komunikācijas analīze 2022. gadā” mērķis ir noskaidrot VAS starptautiskās lidostas “Rīga” mārketinga komunikāciju 2022. gadā, kad tikko pēc pandēmijas ierobežojumiem lidostas darbība bija pilnībā atjaunojusies. Darba teorētiskajā daļā tiek apskatīti tādi jēdzieni kā komunikācija, mārketinga komunikācija, tās būtība un veidi, kā arī mārketinga komunikācijas plānošanas procesi. Bakalaura darba pētījuma veikšanai tika izmantotas trīs pētniecības metodes: kontentanalīze, interneta aptauja, daļēji strukturēta intervija. Darbā iegūtie secinājumi liecina, ka VAS starptautiskās lidostas “Rīga” mārketinga komunikācija 2022. gadā ir bijusi aktīva un pilnībā atguvusies no pandēmijas sekām, taču tika ietekmēta un pielāgota citiem apstākļiem.

The aim of the Bachelor's thesis "Analysis of VAS international airport 'Riga' marketing communication in 2022" is to investigate the marketing communications of Riga International Airport in 2022, when the airport's operations had fully recovered shortly after pandemic restrictions. The theoretical part of the thesis examines concepts such as communication, marketing communication, its essence and types, as well as the processes of marketing communication planning. Three research methods were used to conduct the Bachelor's thesis: content analysis, online survey, and semi-structured interviews. The conclusions drawn from the research indicate that the marketing communication of Riga International Airport in 2022 was active and fully recovered from the effects of the pandemic, but was influenced and adapted to different circumstances.The theoretical part of the thesis examines concepts such as communication, marketing communication, its essence and types, as well as the processes of marketing communication planning. Three research methods were used to conduct the Bachelor's thesis: content analysis, online survey, and semi-structured interviews. The conclusions drawn from the research indicate that the marketing communication of Riga International Airport in 2022 was active and fully recovered from the effects of the pandemic, but was influenced and adapted to different circumstances.
Analysis of VAS international airport "Riga" marketing communication in 2022
Keywords: Komunikācijas zinātne; lidosta; komunikācija; mārketings; sociālie tīkli